2021
DOI: 10.24953/turkjped.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical follow-up of children with high vitamin B12 values: should we worry?

Abstract: Vitamin B12 (cobalamin, Cbl) is one of the most important vitamins that can be dissolved in water. It is absorbed in terminal ileum, transported by haptocorrins and stored in the liver. It is involved in methyl transfer and nucleotide synthesis. In children, deficiency leads to megaloblastic anemia and affects neurologic development. The importance of deficiency in children is well understood. There are many studies about vitamin B12 deficiency. [1][2][3] The widespread use of autoanalysers in hospital laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A limitation of our study was the short follow-up period, which was approximately 1 year in dogs and <2 years in cats, although previous human, cohort-based, retrospective studies identified an association between elevated cobalamin and the development of cancer within a year, 12 hence a 1 year follow up in animals may have been sufficient to observe any effect of hypercobalaminemia on cancer risk. An association between hypercobalaminemia and the development of cancer in children was not observed in previous studies, 13 and although some young animals were included in the present study, only two control dogs and one hypercobalaminemic cat were aged less than 6 months.…”
Section: Discussionmentioning
confidence: 90%
“…A limitation of our study was the short follow-up period, which was approximately 1 year in dogs and <2 years in cats, although previous human, cohort-based, retrospective studies identified an association between elevated cobalamin and the development of cancer within a year, 12 hence a 1 year follow up in animals may have been sufficient to observe any effect of hypercobalaminemia on cancer risk. An association between hypercobalaminemia and the development of cancer in children was not observed in previous studies, 13 and although some young animals were included in the present study, only two control dogs and one hypercobalaminemic cat were aged less than 6 months.…”
Section: Discussionmentioning
confidence: 90%
“…However, unexpected high concentrations are sometimes found in these patients [1]. In the literature, hypervitaminemia B12 (hB12) is considered a relatively common finding, between 7-20% [2], even more than its deficiency. However, despite its prevalence, hB12 is a clearly underestimated analytical abnormality [3].…”
Section: Introductionmentioning
confidence: 99%
“…The aims of our study were [1] to characterize the type of interference in our vitamin B12 immunoassay, [2] to propose an algorithm for the screening of antibody-mediated analytical interferences, and [3] to evaluate the economic impact of the implementation of such an algorithm.…”
Section: Introductionmentioning
confidence: 99%